Macular pigment Raman detector for clinical applications - Ermakov, Igor (2004)
Clinical studies of carotenoid macular pigments (MP) have been limited by the lack of noninvasive, objective instruments. We introduce a novel noninvasive optical instrument, an MP Raman detector, for assessment of the carotenoid status of the human retina in vivo. The instrument uses resonant excitation of carotenoid molecules in the visible wavelength range, and quantitatively measures the highly specific Raman signals that originate from the single- and double-bond stretch vibrations of the π-conjugated carotenoid molecule’s carbon backbone. The instrument is a robust, compact device and suitable for routine measurements of MP concentrations in a clinical setting. We characterized and tested the instrument in clinical studies of human subjects to validate its function and to begin to establish its role as a possible screening test for macular pathologies. We also show that the MP Raman spectroscopy technology has potential as a novel, highly specific method for rapid screening of carotenoid antioxidant levels in large populations at risk for vision loss from age-related macular degeneration, the leading cause of blindness of the elderly in the developed world.